(untitled) (The Journal of Psychology and Sociology, 2019)
This article explores the methods and methodology of transition to new sources of renewable energy – solar energy, hydropower, wind energy and the principles of renewable energy. The aim of the work is to spread knowledge, understanding, competence, analysis – synthesis, evaluation and critical thinking among different segments of the population. Research taking into account globalization, Westernization, Internet culture and turbulence, the requirements of the fourth industrial revolution. The methodology of the research is a sociological survey. On the chosen topic we have studied were conducted in all fourteen regions of the country, as well as in Astana and Almaty: 1600 people older than 18 years were Interviewed. At the same time, 70 percent of them noted that they consider themselves a “citizen of the Republic of Kazakhstan”. The five priority values for our compatriots included health (75.3%), children (54.2), energy security and literacy (44.7), well-being and prosperity (40.9). Relevance and expediency are accused by the fact that this chosen topic is completely undeveloped. As far as we know, there is not even an elementary article on the submitted issue, not speaking about the book. The main results and conclusions of the research work are that energy literacy, knowledge of foreign languages, cultural openness are required. Fortunately, with the energy Maxim competency of our youth is all right, as well as with foreign languages – young people have become much more willing to learn them. But as for energy competence, it is more difficult here. We are talking about the power of socialization. Is it possible in our conditions to bring up this very self-realization associated with the open consciousness that the Republic intends to increase the share of SIE to 50% by 2050. Due to the sun and water, which are many in Kazakhstan, a lot of oil and gas, but especially huge coal reserves. Only wind energy can bring in about 920 billion kWh per year, technically possible to implement the hydro potential is estimated at 62 billion kWh, the potential of solar energy in the southern regions of the country reaches 2500– 3000 solar hours per year. The Republic has large reserves of liquid and solid hydrocarbons, which is esti- mated at 32 billion tons of oil equivalent, or about 3.6% of the world’s primary energy6 as well as uranium. As for uranium deposits, they are classified as strategic subsoil plots, exploration and production of which is a priority right of the state, which it implements through the national company. Therefore, the modernization of public consciousness in accordance with the plan of the nation “100 concrete steps. People should under- stand the advantage of future energy, have energy potential.